The Case Selection for Vaginal Cuff Brachytherapy in Cervical Cancer Patients After Radical Hysterectomy and External Beam Radiation Therapy - Lai, Ying-Lu; Jin, Ye-Ning; Wang, Xi; Qi, Wei-Xiang; Cai, Rong; Xu, Hao-Ping (Frontiers in Oncology, 2021)
Objective To explore the suitable cases for vaginal cuff brachytherapy (VCB) combined with external beam radiation therapy (EBRT) in the postoperative treatment of cervical cancer. Methods We retrospectively analyzed the clinical data of 214 postoperative cervical cancer patients who received radiotherapy from January 2008 to December 2015. Among them, 146 patients received postoperative EBRT, 68 received EBRT plus VCB. There was no statistical difference in clinical and pathological characteristics between these two groups. Those who with negative vaginal cuff underwent supplemented 12–18 Gy/2–3 Fx VCB. Survival analyses were performed using Kaplan–Meier method, and Cox model was used to analyze prognostic factors. Results The median follow-up was 52 months (9–136 months), and 4-year RFS (recurrence-free survival) was 77%. Among them, 58 patients (27.10%) had local or distant recurrences, 29 (13.55%) in pelvis, six (2.80%) with metastases to para-aortic, 19 (8.88%) with distant metastases (including inguinal lymph nodes) and four (1.87%) with both local and distant recurrences. The postoperative brachytherapy boost did not improve RFS or OS (overall survival) among the investigated subjects, P = 0.77, P = 0.99, respectively. Neither it decreased the local relapse in the pelvis or vaginal cuff, P = 0.56, P = 0.59. Subgroup analyses showed that brachytherapy boost improved RFS in patients who had bulky mass (>4 cm) as well as 1) with deep stromal invasion (>50% stromal invasion), P = 0.012 or 2) received low EBRT dose (≤45 Gy), P = 0.033, and in patients with deep stromal invasion as well as received low EBRT dose (P = 0.018). Conclusions We first proposed the case selection model for postoperative EBRT plus VCB. Brachytherapy boost were considered in the setting of postoperative radiotherapy if the patients had at least two out of these following factors: bulky mass, deep stromal invasion and low EBRT dose.